1990
DOI: 10.1111/j.1756-1051.1990.tb01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐bearing chrysophytes from tropical Northeast India

Abstract: 1990. Scale-bearing chrysophytes from tropical Northeast India. -Nord. J. Bot. 10: 343-354. Copenhagen. ISSN 0107-055x. This is the first publication describing scale-bearing Chrysophyceae from India by means of electron microscopy. 'henty seven such taxa are described from samples for ponds, rivers and thermal springs. 'henty of these are Mallomonas spp.: M . akrokomos, M. bronchartiana, M . caudata, M . ceylanica, M. costata, M. crassisquama, M. cyathellata var. cyathellata, M. cyathellata var. chilensis, M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 11 publications
2
46
0
Order By: Relevance
“…All 12 isolated strains of S. hibernica originated from nutrient-poor localities, with conductivity values ranging between 23-87 µS cm −1 (Table 1). To our knowledge, all records of S. australiensis have been associated with clear, oligotrophic water bodies (Croome & Tyler, 1985;Cronberg, 1989Cronberg, , 1996Saha & Wujek, 1990;Wee et al, 1993;Hansen, 1996). The measured conductivity of these water samples was 10-123 µS cm −1 .…”
Section: Species Delineation and Morphological Evolutionmentioning
confidence: 99%
“…All 12 isolated strains of S. hibernica originated from nutrient-poor localities, with conductivity values ranging between 23-87 µS cm −1 (Table 1). To our knowledge, all records of S. australiensis have been associated with clear, oligotrophic water bodies (Croome & Tyler, 1985;Cronberg, 1989Cronberg, , 1996Saha & Wujek, 1990;Wee et al, 1993;Hansen, 1996). The measured conductivity of these water samples was 10-123 µS cm −1 .…”
Section: Species Delineation and Morphological Evolutionmentioning
confidence: 99%
“…However, claims of endemicity should be treated cautiously. Some species of Mallomonas and Synura regarded as Australian endemics (Croome & Tyler, 1983b-c, 1985a) have since been located in the tropics (Asmund & Kristiansen, 1986;Saha & Wujek, 1990). Illustrations and further details of unique Australian freshwater algae can be found in Tyler & Wickham (1988 and references).…”
mentioning
confidence: 99%
“…In North America, rich and diverse floras of synurophytes have been documented from subtropical localities in Florida (Wujek, 1984a;Wujek and Bland, 1991;Siver and Wujek, 1993;Siver and Lott, 2006) and Louisiana (Wee et al, 1993). Similarly, even though scaled chrysophytes comprise a larger percentage of the annual phytoplanktonic biomass of oligotrophic and mesotrophic lakes (see the discussion below), ample studies demonstrate that large numbers of species also can be found in more eutrophic sites (Kristiansen, 1985(Kristiansen, , 1988b(Kristiansen, , 2005Hickel and Maass, 1989;Gutowski, 1989Gutowski, , 1997Saha and Wujek, 1990). For example, Kristiansen and Tong (1989) and Kristiansen (1985) recorded 40 and 33 taxa of scaled chrysophytes in highly eutrophic ponds in China and Denmark, respectively.…”
Section: B Primary Habitat Requirementsmentioning
confidence: 98%
“…Based on literature records Siver (1991a) Conrad, and to a lesser extent, M. elongata, and M. pseudocoronata, to be more common in eutrophic localities. M. heterospina is often reported from dung or waterfowl-contaminated ponds (Harris and Bradley, 1957;Kristiansen, 1986;Siver, 1991a), and there appears to be ample evidence that M. matvienkoae (Saha and Wujek, 1990;Siver and Vigna, 1997) and M. oviformis (Wei and Yuan, 2001) are also common in eutrophic habitats. S. sphagnicola (Kristiansen, 1986;Siver, 1988a) and S. spinosa f. longispina Petersen & Hansen (Dürrschmidt, 1982;Siver, 1987) are other oligotrophic indicators, while S. curtispina (Petersen & Hansen) Asmund (Gutowski, 1989;Santos and Leedale, 1993;Siver and Marsicano, 1996) is often observed to tolerate eutrophic conditions.…”
Section: E Distribution Along a Trophic Gradientmentioning
confidence: 99%